UPAYA MENINGKATKAN PEMBANGUNAN EKONOMI MELALUI LOCO TOUR UNTUK MENGEMBANGKAN POTENSI WISATA BLORA - Kristiani, Kristiani; Sudarwanto, Al Sentot; Iskamto, Bambang (ED EQUILIBRIUM, 2013)
The purposes of this study are to reveal the natural potential to be developed as a natural tourist attraction, tours loco condition, condition of facilities, accessibility of natural tourist attractions, tourist activities undertaken visiting tourists, business activities in the field of nature tourism that can improve the community economy , and Department policy strategies in developing Perhutani loco tour as an effort to increase tourism and conservation of natural teak forests in Blora. This research was based on the development and nature ekploratif with data collection techniques with questionnaires, in-depth interviews, participant observation, and analysis of documents / archives. The validity of data the used peerdebriefing, triangulation of data and informants review the analysis techniques with interactive models. Conclusions The study showed that the potential of existing natural potential maximum but not enough developed, condition loco tour, physically feasible for use as tourist transportation management but it is not managed properly, the condition and accessibility of support facilities have comprehensive facilities and many of fasilities are not well cared for and destroyed, tourists visiting just to see and enjoy nature tourism, local arts and local foods, as well as the lack of cooperation between loco tour manager in this case KPH Perhutani DepartmentCepu with District Government, Department of Tourism, private, and communities Keywords: Economics, Loco Tour, Ecotourism